INNOVATIVE TECHNOLOGIES AND TOOLS OF DISTANCE LEARNING IN THE PROFESSIONAL EDUCATION OF MANAGERS - Gorodianska , Larysa (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article explores the essence and content of innovative technologies and tools of distance learning in the professional education of managers. The theoretical and methodological foundations of integrating information and communication technologies into the system of training future management professionals are defined. The main innovative technologies (learning management systems, virtual learning environments, business simulations, artificial intelligence, and Big Data) and distance learning tools (electronic resources, online courses, interactive communication tools) are considered. Practical aspects of their implementation are emphasized, including the experience of higher education institutions in Ukraine and abroad, as well as key challenges and problems such as technical, organizational, and psycho-pedagogical barriers. The role of innovative technologies in shaping managerial, communicative, and digital competencies of managers is substantiated. It is concluded that innovative distance learning is a crucial factor in improving the quality of professional education and the competitiveness of future managers in the digital economy.